Short-term overeating results in incomplete energy intake compensation regardless of energy density or macronutrient composition - Apolzan, John W. (2013)
OBJECTIVE: To evaluate the effects of overeating (140% of energy requirements) a high-fat low-energy density diet (HF/LED, 1.05kcal/g), high-fat high-energy density diet (HF/HED, 1.60kcal/g), and high-carbohydrate (HC) LED (1.05kcal/g) for 2-days on subsequent 4-day energy intake (EI), activity levels, appetite, and mood. DESIGN AND METHODS: Using a randomized cross-over design, energy expenditure and EI were standardized during overeating. RESULTS: In 20 adults with a mean±SD BMI of 30.7±4.6kg/m(2), EI was not suppressed until the second day after overeating and accounted for ~30% of the excess EI. Reductions in EI did not differ among the 3 diets or across days. Overeating had no effect on subsequent energy expenditure but steps/day decreased after the HC/LED and HF/HED. Sleep time was increased after the HF/HED compared to both LEDs. After overeating a HF/HED vs. HF/LED, carbohydrate cravings, hunger, prospective food consumption, and sadness increased and satisfaction, relaxation, and tranquility decreased. CONCLUSIONS: Diet type, time, or their interaction had no impact on compensation over 4 days. No adaptive thermogenesis was observed. The HF/HED vs. HF/LED had detrimental effects on food cravings, appetite, and mood. These results suggest short-term overeating is associated with incomplete compensation.